Пролетали лебеди: рассказы / Ф. А. Абрамов ; сост. В. М. Акимов - Абрамов Федор Александрович (Детская литература, 1989)
Экземпляры: (20220520) / Инвентарный номер: 18423zzzz / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 16 / ББК: 84(2Рос=Рус)6